Substitution effect of Cr3+ on hyperfine interactions, magnetic and optical properties of Sr-hexaferrites. Issue 13 (September 2018) - Slimani, Y.; Baykal, A.; Amir, Md.; Tashkandi, N.; Güngüneş, H.; Guner, S.; El Sayed, H.S.; Aldakheel, F.; Saleh, T.A.; Manikandan, A.
Abstract: Chromium-substituted strontium nano-hexaferrites, SrCrx Fe12-x O19 (0.0 ≤ x ≤ 1.0), were produced by the hydrothermal route. The structure, morphology, optical and magnetic properties were studied. Crystal structure, spinel phase and functional groups were verified using X-ray diffraction and Fourier Transform Infrared spectroscopy. The average crystallites size is ranging between 50 and 67 nm. Scanning electron microscopy observations indicated that the multi-grains of the particles are aggleromated and are hexagonal in shape. The isotherm plots obtained from the nitrogen physisorption experiments showed that the mesopore area and the total pore volume decreased progressively with increasing the Cr 3+ content. Besides, the band gap energy (Eg ) decreases from 1.75 to 1.43 eV. The magnetic hysteresis loops showed that the produced nano-hexaferrites exhibit hard ferromagnetic-like (FM) behavior. Compared to the pristine SrFe12 O19 product, the deduced saturation (Ms ) and remanent (Mr ) magnetizations, the coercivity (Hc ) and the magnetocrystalline anisotropy field (Ha ) increase for lower Cr 3+ content (x ≤ 0.4) and then decrease as the Cr 3+ content further increases. The squareness ratio Mr /Ms are ranging between 0.5 and 0.6, suggesting the single domain nano-sized particles with uniaxial anisotropy for various synthesized products. Mossbauer analysis was done to determine the quadrupole splitting, the isomer shift, and the hyperfine magnetic field values of all products.